“Community Work” in a Climate of Adaptation: Responding to Change in Rural Alaska - Loring, Philip A; Gerlach, S. Craig; Penn, Henry J (Human ecology : an interdisciplinary journal, 2016)
We draw on our research experiences with municipal workers in Alaska, where the impacts of climate change are already extensive, to examine adaptation and related concepts, such as resilience and vulnerability, which have become widely used in science and policy formulation for addressing climate change despite also being subject to multiple critiques. We use local people’s experiences with environmental challenges to illustrate limitations of the climate change adaptation paradigm, and offer the additional concept of “community work” — analogous to niche construction — as a counterpart to the adaptive process at the community level. Whereas climate change adaptation insinuates active and purposive change, the reality we have repeatedly encountered is that people in these communities focus not on changing but on building and maintaining capacity and achieving stability: keeping aging and overtaxed infrastructure running while also working toward improving quality of life and services in their communities. We discuss how these findings are congruent with recent calls to better situate climate change adaptation policy in the context of community development, and argue that scientists and policymakers need to understand this context of community work to avoid the pitfalls that potentially accompany the adaptation paradigm.